Accessibility analysis in evaluating exposure risk to an ecosystem disservice. (December 2019) - Ala-Hulkko, Terhi; Kotavaara, Ossi; Alahuhta, Janne; Kesälä, Mikko; Hjort, Jan
Abstract: Ecosystem services are fundamental to the well-being and health of people. Despite the growing awareness of the positive impacts of ecosystem services on human health, researchers have often ignored many ecosystem functions that are disadvantageous to humans. These negative facets of ecosystems are called ecosystem disservices. The central focus of this study was to test the applicability of Geographic Information Systems-based spatial accessibility analysis in mapping the potential risk of ecosystem disservice at a national scale. We used tick exposure as an example of a disservice. Worldwide, ticks (genus Ixodes ) are the primary vectors of several dangerous diseases which pose threats to people. As the probability of encountering infectious ticks has increased during the last decades, new spatial information on high-risk tick exposure areas are needed. To evaluate exposure risk, we developed a tick probability map based on tick observations and environmental variables in Finland. First, we analyzed what kind of threat ticks pose to populations in residential areas and around free-time residences. Second, we studied if the movement of people (here school children) in the everyday environment increased tick exposure risk. We calculated the shortest school route for all children by using spatial accessibility analysis. Our results showed that taking the movement of people into consideration through the accessibility analysis, we can get a more realistic picture of tick exposure risk. Further, we gained a better overview of the number of children at higher exposure risk. This kind of information is crucial for pre-assessment and identification of public health strategies for control and minimizing tick-borne diseases. In general, the accessibility approach provided a good overview of areas where the greatest tick exposure was present and produced valuable information to support decision-making. The method enabled new insights into the assessment of exposure to ecosystem disservices. Highlights: Spatial accessibility gives new insights into assessing exposure to disservices. We analyze potential tick contacts and activity of people in high-risk areas. This kind of information is crucial for control and minimizing tick-borne diseases.